Cytosine methylated DNA synthesized by Taq polymerase used to assay methylation sensitivity of restriction endonuclease HinfI. - Colasanti, J (1991)
We have studied the resistance of cytosine methylated DNA to digestion by the restriction endonuclease HinfI, using a simple PCR procedure to synthesize DNA of known sequence in which every cytosine is methylated at the 5 position. We find that HinfI cannot digest cytosine methylated DNA at the concentrations normally used in restriction digests. Complete digestion is possible using a vast excess of enzyme; under these conditions, the rate of HinfI digestion for cytosine methylated DNA is at least 1440-fold slower than for unmethylated DNA. The presence of an additional methylated cytosine at the degenerate position internal to the recognition sequence does not appear to increase the resistance to HinfI digestion. We also tested HhaII, an isoschizomer of HinfI, and found that it is completely inactive on cytosine methylated DNA. The procedure we have used should be of general applicability in determination of the methylation sensitivities of other restiction enzymes, as well as studies of the effects of methylation on gene expression in direct DNA transfer experiments.